Effect of Moderate Aerobic Exercise on Complement Activation Pathways in Polycystic Ovary Syndrome Women - Ramanjaneya, Manjunath; Abdalhakam, Ibrahem; Bettahi, Ilham; Bensila, Milin; Jerobin, Jayakumar; Aye, Myint Myint; Alkasem, Meis; Sathyapalan, Thozhukat; Atkin, Stephen Lawrence; Abou-Samra, Abdul-Badi (Frontiers in Endocrinology, 2022)
Background: The complement system is pivotal in host defense mechanisms, protecting against pathogenic infection by regulating inflammation and cell immunity. Complement related protein activation occurs through three distinct pathways: classical, alternative, and lectin dependent pathways, which are regulated by cascades of multiple proteins. Complement activation is recognized in polycystic ovary syndrome (PCOS) to be associated with obesity and insulin sensitivity. Exercise reduces insulin resistance and may help reduce obesity and therefore this study was undertaken to determine the effect of exercise on the activation of complement related proteins in PCOS and control women. Subjects and Measurements: In this study ten controls and eleven PCOS subjects who were age and weight matched underwent an 8week supervised exercise program at 60% maximal oxygen consumption. Weight was unchanged though insulin sensitivity was increased in PCOS and controls. Fasting baseline and post exercise samples were collected and 14 complement related proteins belonging to classical, alternative and lectin dependent pathways were measured. Results: Baseline levels of Complement C4b and Complement C3b/iC3b were higher in PCOS (P<0.05) compared to controls. Exercise reduced complement C1q (P<0.05), C3 (P<0.001), C4 (P<0.01), factor B (P<0.01), factor H (P<0.01) and properdin (P<0.05 ) in controls, but not in PCOS women. Conclusion: Exercise induced complement changes in controls that were not seen in PCOS subjects suggesting that these pathways remain dysregulated even in the presence of increased insulin sensitivity, and not improved by moderate aerobic exercise.